Looking Beyond the Provision of Injecting Equipment to People Who Use Anabolic Androgenic Steroids: Harm Reduction and Behavior Change Goals for UK Policy. (June 2021) - Bates, Geoff; McVeigh, Jim; Leavey, Conan
Understanding of the choices and motivations of people who use anabolic androgenic steroids (AAS) for muscular enhancement has increased greatly in the past thirty years, along with understanding of a wide range of health harms associated with this form of drug use in the community. During this period the predominant public health intervention for this population in the UK has consistently remained the provision of injecting equipment to prevent blood borne virus (BBV) transmission. The study explored the health professionals' and other stakeholders' perceptions on: whether the current UK public health response is sufficient to address the needs of people who use AAS, and if not, what other needs they might have. This included an exploration of whether there were gaps in harm reduction strategies or other behavioral outcomes and interventions that were needed. Interviews with 27 stakeholders who provide support to people who use AAS in a variety of roles established consensus on the need for a range of interventions to reduce harm and risk in those that choose to use AAS, to prevent initiation, to motivate and support cessation, and to prevent relapse. Study findings indicate that while providing sterile injecting equipment remains essential, it should be considered a bare minimum. The challenge is to develop and deliver a range of harm reduction interventions that look beyond BBV prevention to provide appropriate support to who choose to use AAS at all points in their cycles of use and ultimately for those choosing the temporary or permanent cessation of use.